Performative læringsrum på digitale scener - dramadidaktik og sociale medier - Kristian Nødtvedt Knudsen (Cappelen Damm Akademisk NOASP, 2017)
The constant presence of Social Media has left its mark on schools and other educational institutions. It can be a challenge for the teacher to find ways to integrate the social and digital spaces in an educational context. In this study, I explore how performative learningspaces arise in the crossover between teaching and learning drama and social media. The study uses data from a workshop designed and implemented by the author with 89 high school students from Trondheim in the autumn of 2015. In the workshop, I try to implement a performative and postmodern view on the subject and on knowledge production. The article discusses the dramaturgical principles that are present in the workshop and utilizes the dramaturgical thinking as an analytical tool in the inquiry of the performative learning spaces. In conclusion, I discuss what performative learning spaces can bring to drama in education and education in genereal. The term "performative learning spaces" is not an established concept neither in teaching and learning drama or in arts in education. The study should thus be seen as an attempt to define such a concept.